Pastoral Keluarga Sebagai Upaya Membangun Keterlibatan Hidup Menggereja Umat Stasi Santo Matius Bentot - Grasia Rosalina; Silvester Adinuhgra; Agnes Angi Dian Winei (Sepakat : Jurnal Pastoral Kateketik, 2023)
This text discusses the results of research related to family pastoral activities aimed at building the involvement of the faithful in the life of the Saint Matthew community in Bentot village, within the Parish of Saint Michael Tamiang Layang under the Diocese of Palangka Raya. The research employed a qualitative descriptive approach. The study was conducted in Saint Matthew community, Bentot village, for a duration of 14 days during the month of June 2023. The research involved 11 participants, including one Sunday school student, three young Catholics, two pastoral workers or catechists, three parents, one community leader, and the parish priest. The collected data was analyzed using the Miles and Huberman method. The findings of the research indicate the limited involvement of the faithful in church life, various hindering factors, and the expectations of the faithful regarding the parish's program to enhance involvement, faith development, and family harmony. The community in Saint Matthew, Bentot village, hopes for additional specialized programs to nurture and develop faith and understanding through catechesis and retreats focusing on marriage and family themes.